A system dynamics analysis to improve self-sufficiency level for rice security policy in Malaysia - Alias, Emmy Farha (2013)
The production of paddy in Malaysia showed a relatively higher rate of growth during the Green Revolution era and began to decline in the 1990s and beyond, indicating a logistic growth between 1970 and 2010. The annual paddy productivity growth has declined to 0.59% in 2012 compared to 3.6% in the 1970s. This non-linear rice production behaviour over time implies a structural change that has occurred in the industry. By the late 1990s, these high growth rates were not maintained due to the reduction in the productivity growth. The productivity was not sustained due to a number of factors. These include; limited area expansion due to urbanisation, outflow of resources due to the pull from the lucrative non-agricultural sectors,limited improvement in value-added, unsustainable farm practices, lack of infrastructures and limited technological advancement. The general objective of this study is to examine the food security of paddy and rice industry in Malaysia under a changing macro-economic environment. The specific objectives are (i) to understand the structure and behavior of paddy and rice industry; (ii) to develop a system dynamics model for paddy and rice sector; (iii) to simulate a number of scenarios and their impacts on the sustainability on food security i.e., self sufficiency level (SSL) targets; and (iv) to recommend alternative policies towards a sustainable food security in Malaysia. A paddy and rice system dynamics model was developed to study and understand the behavior of the paddy and rice industry. The model was divided into two sub models; (i) paddy production (paddy area, productivity and input); and (ii) consumption (income and consumption). The study also identified four policy framework; (i) land management to regulate conversion of paddy area to other agricultural and non-agricultural activities; (ii) physical loss during post-harvest period; (iii) promoted organic fertilizers to improve soil structure and fertility; and (iv) structural change in determining the desired paddy productivity.The study simulated six scenarios; Scenario 2 represents the withdrawal of subsidies, Scenario 3 adds the effect of post-harvest losses, Scenario 4 includes paddy land conversion, Scenario 5 examines implementation of organic farming, and lastly Scenario 6 incorporates structural change in determining the desired paddy productivity. The simulation exercise suggests that Malaysia is able to achieve SSL of 62% in Scenarios 2 and 3 and 67% in Scenarios 4 and 5. However, under Scenario 6, SSL achieved is estimated at 80% by 2050. This is largely due to the higher growth in domestic rice production as a result of the combination of policies implemented (withdrawal of subsidies, post-harvest losses technology, land management, organic farming and structural change in determining the desired paddy productivity).